Exploring intergenerational links and genetic correlates of metacognitive beliefs: A systematic review and meta-analysis - De Francesco, Stefano; Fagnani, Corrado; Medda, Emanuela; Palmieri, Sara; Mansueto, Giovanni; De Munari, Giacomo; Caselli, Gabriele; Scaini, Simona (Frontiers in Psychiatry, 2025)
BackgroundMetacognitive beliefs, as proposed in the Self-Regulatory Executive Function (S-REF) model, are considered to play a central role in the development and maintenance of psychological disorders; however the intergenerational dimension of these beliefs remains poorly understood. Existing studies suggest potential associations between parental and offspring metacognitive beliefs, while preliminary genetic evidence indicates that some domains may be more strongly influenced by biological predispositions.MethodsA systematic search of PubMed, EBSCOhost, and SCOPUS was conducted between January and April 2025, examining studies assessing the association between parental and offspring metacognitive beliefs, as described in the S-REF model, and studies exploring links with genotype. Effect sizes were pooled for domains assessed in at least three studies, and moderator analyses considered age, study quality, and the number of covariates included.ResultsNine studies met inclusion criteria, eight focusing on parent–child associations and one on genotype. Meta-analytic results indicated small-to-moderate associations for positive metacognitive beliefs (r = .24) and negative beliefs about danger and uncontrollability of thoughts (r = .17), whereas Cognitive self consciousness did not show significant associations. Limited molecular genetic evidence suggested that Cognitive confidence and Need to control thoughts may be more strongly linked to biological predisposition. Heterogeneity was observed across studies, and moderator analyses did not reveal significant effects.ConclusionThe intergenerational dimension of metacognitive beliefs is an underexplored area with heterogeneous findings. Associations between parental and offspring beliefs are evident, particularly for Positive and Negative metacognitive beliefs, while some domains may reflect biological influences. Future research should employ longitudinal designs, comprehensive assessment across all metacognitive domains, and integrate both genetic and environmental factors to clarify the mechanisms underlying these associations.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251020891.